A meta-analysis of the efficacy of nonphysician brief interventions for unhealthy alcohol use: implications for the patient-centered medical home. - Sullivan, Lynn E; Tetrault, Jeanette M; Braithwaite, R Scott; Turner, Barbara J; Fiellin, David A (The American journal on addictions / American Academy of Psychiatrists in Alcoholism and Addictions, 2011)
Brief physician interventions can reduce alcohol consumption. Physicians may not have the time to provide brief interventions, and it is unclear whether nonphysicians can do so effectively. We conducted a systematic review and meta-analysis to examine the efficacy of brief interventions by nonphysician clinicians for unhealthy alcohol use. We searched the English-language literature in MEDLINE and other databases covering the domains of alcohol problems, primary care, nonphysician, and brief interventions. Studies of brief interventions delivered at least in part by nonphysicians in primary care and examining drinking outcomes were included. Sensitivity analyses examined the effect of excluding studies that contributed disproportionately to the heterogeneity of results. Thirteen studies, conducted 1996-2008, met our criteria. Seven studies with a total of 2,633 patients were included in the meta-analysis. Nonphysician interventions were associated with 1.7 (95% confidence interval [CI]=-.03 to -3.5) fewer standard drinks per week than control conditions (p = .054). Excluding the one study that increased heterogeneity, the effect was smaller but reached statistical significance; nonphysician counseling was associated with 1.4 (95% CI = .3- 2.4) fewer standard drinks per week compared to control (p = .012). Nonphysician brief interventions are modestly effective at reducing drinking in primary care patients with unhealthy alcohol use.
Keywords: Alcohol Drinking; Behavior Control; Directive Counseling; Humans; Medical Staff; Patient Participation; Patient-Centered Care; Primary Health Care; Staff Development; Treatment Outcome